Small peptide-based GLP-1R ligands: an approach to reduce the kidney uptake of radiolabeled GLP-1R-targeting agents? - Veronika Barbara Felber (EJNMMI Radiopharmacy and Chemistry, 2021)
Abstract Aim Elevated kidney uptake in insulinoma patients remains a major limitation of radiometallated exendin-derived ligands of the glucagon-like peptide 1 receptor (GLP-1R). Based on the previously published potent GLP-1R-activating undecapeptide 1, short-chained GLP-1R ligands were developed to investigate whether kidney uptake can be reduced by means of direct 18F-labeling (nuclide-based accelerated renal excretion) or the reduction of the overall ligand charge (ligand-based reduced kidney uptake). Materials & methods GLP-1R ligands were prepared according to optimized standard protocols via solid-phase peptide synthesis (SPPS) or, when not practicable, via fragment coupling in solution. Synthesis of (2‘-Et, 4‘-OMe)4, 4’-L-biphenylalanine ((2′-Et, 4′-OMe)BIP), required for the preparation of 1, was accomplished by Suzuki-Miyaura cross-coupling. In vitro experiments were performed using stably transfected GLP-1R+ HEK293-hGLP-1R cells. Results In contrast to the three reference ligands glucagon-like peptide 1 (GLP-1, IC50 = 23.2 ± 12.2 nM), [Nle14, Tyr(3-I)40]exendin-4 (IC50 = 7.63 ± 2.78 nM) and [Nle14, Tyr40]exendin-4 (IC50 = 9.87 ± 1.82 nM), the investigated GLP-1R-targeting small peptides (9–15 amino acids), including lead peptide 1, exhibited only medium to low affinities (IC50 > 189 nM). Only SiFA-tagged undecapeptide 5 (IC50 = 189 ± 35 nM) revealed a higher affinity than 1 (IC50 = 669 ± 242 nM). Conclusion The investigated small peptides, including lead peptide 1 , could not compete with favorable in vitro characteristics of glucagon-like peptide 1 (GLP-1), [Nle14, Tyr(3-I)40]exendin-4 and [Nle14, Tyr40]exendin-4. The auspicious EC50 values of 1 provided by the literature could not be transferred to competitive binding experiments. Therefore, the use of 1 as a basic scaffold for the design of further GLP-1R-targeting radioligands cannot be recommended. Further investigations might include the scaffold of 5, although substantial optimizations concerning affinity and lipophilicity would be required. In sum, GLP-1R-targeting radioligands with reduced kidney uptake could not be obtained in this work, which emphasizes the need for further ligands addressing this particular issue.